Factors Influencing Stock Prices in Coal Sub-Sector Companies Listed on the IDX for the 2019-2023 Period - Anisa, Siti; Nur’atin, Atin; Budianto, Erwin (Ridwan Institute, 2025)
This study examines the factors influencing stock prices of coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, focusing on three key financial ratios: Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA). The research employs quantitative methods to analyze the relationship between these financial ratios and stock prices. The results indicate that while CR and DER do not have a significant impact on stock prices, ROA shows a positive and significant relationship with stock prices. This suggests that better asset management and profitability, as reflected in ROA, enhance investor confidence, thereby driving stock prices higher. The findings contribute to the understanding of how financial ratios influence the stock performance of coal companies in Indonesia, offering valuable insights for investors making informed investment decisions. The implications of this research highlight the importance of focusing on profitability and asset management when evaluating the financial health of companies in the coal sector, particularly for investors looking to make strategic investment choices based on financial metrics.